Vulneración de los derechos humanos en la redacción de noticias de la sección de crónica roja de diario El Nacional de la ciudad de Machala, en el primer semestre del año 2014. - Palma Maza, Tania Paola (2015)
This research is the result of efforts of a group of young entrepreneurs interested in deepening and enhancing their knowledge in the area of social communication. The overall objective of this thesis is to analyze, using the methodology of quantitative analysis.